A Systematic Review of Innovative Teaching Strategies in Science: Exploring Hands-on Learning, Technology Integration, and Student-Centered Approaches - Laid, Shella Mae Tanghian; Adlaon , Mauricio S. (Tecno Scientifica Publisher, 2025)
This systematic review examined the effectiveness of innovative teaching strategies in science education, focusing on hands-on learning, technology integration, and student-centered approaches. Using the PRISMA framework, 18 peer-reviewed studies from 2020 to 2025 were analyzed to identify trends, benefits, and challenges. Findings revealed that hands-on learning enhanced engagement and problem-solving skills but faced resource constraints. Technology integration improved accessibility and visualization but required teacher training and equitable access. Student-centered approaches promoted critical thinking and collaboration but demanded alternative assessment methods. Addressing these challenges through blended learning and policy support was found to enhance science education outcomes.